The Role of Policies Made by the Government Towards Empowering Local Communities - Achmad, Willya (International Journal of Science and Society, 2024)
Empowering local communities is an important aspect in the sustainable development of a country. This research aims to analyze the role of policies that have been made by the Government in the context of empowering local communities. Through a qualitative approach and case studies, this research will explore the implementation and impact of these policies on increasing the capacity, participation and welfare of local communities. The research results highlight the role of government policy clusters in empowering local communities, which involves providing resources, access to education, and creating a supportive environment. Although the cluster had a significant positive impact in increasing the economic independence and quality of life of local communities, challenges related to slow bureaucracy, corruption and policy changes were also identified. In this context, active participation of local communities is recognized as a key element, however, more effective policy implementation requires strong commitment and cooperation between government and communities. By building inclusive and transparent relationships, government policies can be more responsive to the unique needs of each community, creating a solid foundation for local community empowerment and sustainable progress nationally.